Synthesis and Configuration of Neomaclafungin A. Issue 17 (11th August 2017) - Zhu, Shijun; Wu, Yikang
Abstract: The relative and absolute configuration of neomaclafungins were impossible to establish by spectroscopic analyses alone because of the lack of exploitable 1 H‐ 1 H couplings and nOes between the upper and the lower subunits. This very difficult task now is finally completed by an enantioselective total synthesis of neomaclafungin A (revised) and its diastereomer (reported). The results also provided a key reference for the complete structures for other neomaclafungins and the long‐known closely related natural product maclafungin. Abstract : Although the relative configurations of the upper and lower fragments of neomaclafungin A were assigned, establishment of the configuration for the whole molecule remained impossible because of the lack of exploitable 1 H‐ 1 H couplings between the two fragments. Now the problem has been solved by an enantioselective total synthesis. Some interesting relative configuration‐dependent reactivity differences were also observed en route to the total synthesis.